Greenland, Kjerulf Fjord through to Dicksons Fjord and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background Scoop Mountain. In foreground Hisinger Glacier [Hisinger Gletscher] - coming from the south, curves to left (N.E.) under shadow of the northern side of Scoop Mt. [mountain] and makes steep descent into Dickson [Dicksons] Fjord. Photo taken at 4:55 P.M., looking S.E. from high point of land on S.E. side of southern terminal of range of mts. [mountains] which have formed eastern side of Kjerulfs [Kjerulf] Fjord. Red line denotes L.A.B. route August 6.